PERTANGGUNGJAWABAN PIDANA TERHADAP CALON PENGEMUDI SAAT BELAJAR MENGEMUDI ATAS PELANGGARAN KECELAKAAN LALU LINTAS MENURUT UNDANG UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Jauhari, Louis; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Problems often arise in traffic one of them is the problem of the prospective driver's negligence while learning to drive on the highway, causing a traffic accident. However, the prospective driver's negligence is responsible for the driver instructor in accordance with Law No. 22 of 2009 on Road Traffic and Road Transport and incompatible with Article 2 of the Code of Criminal Justice Act that apply to the perpetrators of such crime. In this case relates to Criminal Liability Candidates Against Motorists When Learning Driving Violations Over Traffic Accidents According to Law No. 22 of 2009 on Road Traffic and Road Transport. The purpose of this skripsi, namely; The first, How sentence imposed for violations of traffic accidents to the candidate driver when learning to drive, second, how to overcome the dualism between the application of Article 79 paragraph (2) of Law No. 22 of 2009 on Road Traffic and Road Transport with the criminal theory Article 2 of the Code of Criminal Justice Act. This type of research can be classified into types of normative juridical research, because this research penulismeneliti library materials or secondary formulated Normative Or Research Book Research book story. From in nature this research is description research that aim to describe clearly and in detail that in this case the author selecting research on the differences of rules and principles hukum.Sumber data used, study libraries or documentary studies. From the results of this study concluded. First, the driving school has not reached the expected level in terms of skilled graduates to obtain and understand the essence of safe driving in highway, motorists are often negligent in driving a vehicle that can cause traffic accidents. Thereby, in Act No. 22 of 2009 Article 79 is a special clause for prospective drivers who learned driving and istrukturnya, thenspecialis derogat legi generali, Second, Lex specialis derogat legi generaliasalkan with the terms of the prospective driver to act is in conformity with the beacon -rambu which have been determined in learning driving. Suggestions writer, first, is expected omission of sentences for perpetrators of traffic accidents in the law more clearly so as not to give rise to legal interpretation, Second, efforts to avoid dualism application of the law by revising the legislation in detail and spsesifik avoid misinterpretation in the future .Keywords: Responsibility- Accident- Candidate Driver – Instructor Driver- Traficc.